Cognitive and neuronal bases of expertise - Campitelli, Guillermo (2003)
This thesis examines the cognitive and neural bases of expertise. In so doing, several psychological phenomena were investigated-imagery. memory and thinking-using different tasks, and a variety of techniques of data gathering, including standard behavioural experiments, questionnaires, eye-movement recording, and functional magnetic resonance imaging (fMRI).